The 7Be(d, α)5Li(p α) and 7Be(d, p)8Be*(p 7Li) reactions at 5 MeV/u - Samanta, S.; Gupta, D.; Ali, Sk M.; Mitra, R.; Kundalia, K.; Maity, S.; Ghosh, N.; Saha, S. K.; Tengblad, O.; Perea, A.; Martel, I.; Cederkall, J. (Nuclear Physics A, 2026)
The 7Be(d, α)5Li and 7Be(d, p)8Be*(p 7Li) reactions are studied at 5 MeV/u in the context of the cosmological lithium problem. This work aims to probe the contribution of 7Be destruction mechanisms, particularly through channels that populate intermediate unbound states of 5Li and 8Be. The contribution of 7Be(d, α)5Li(p α) reaction is separated from the 7Be(d, p)8Be*(2α) reaction. The 7Be(d, p)8Be*(p1 7Li*) channel is also identified and is useful for an indirect study of the 7Be(n, p1)7Li* reaction.
Keywords: Be destruction; BBN; Lithium anomaly